2019
DOI: 10.1093/hmg/ddz181
|View full text |Cite
|
Sign up to set email alerts
|

Spp1 (osteopontin) promotes TGFβ processing in fibroblasts of dystrophin-deficient muscles through matrix metalloproteinases

Abstract: Abstract Duchenne muscular dystrophy (DMD) is caused by mutations in the gene encoding dystrophin. Prior work has shown that DMD progression can vary, depending on the genetic makeup of the patient. Several modifier alleles have been identified including LTBP4 and SPP1. We previously showed that Spp1 exacerbates the DMD phenotype in the mdx mouse model by promoting fibrosis and by skewing macrophage polarization. Here, we studied the mechanisms involved in Spp1's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 43 publications
4
44
0
Order By: Relevance
“…A recent study has shown that inhibition of Spp1 expression can inhibit cell proliferation, which is a potential target for cancer therapy. Besides, scientists indicated that the postnatal inhibition of Spp1 can reduce fibrosis and facilitate motor function in DMD (Duchenne muscular dystrophy) mice through promoting TGF- β [ 19 ]. Also, the decrease of Spp1 expression induced by ischemia can damage neovascularization, while the overexpression of Spp1 can increase angiogenesis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that inhibition of Spp1 expression can inhibit cell proliferation, which is a potential target for cancer therapy. Besides, scientists indicated that the postnatal inhibition of Spp1 can reduce fibrosis and facilitate motor function in DMD (Duchenne muscular dystrophy) mice through promoting TGF- β [ 19 ]. Also, the decrease of Spp1 expression induced by ischemia can damage neovascularization, while the overexpression of Spp1 can increase angiogenesis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…To further understand the molecular features of the ve sub-clusters of macrophages mentioned above, we conducted a DEG analysis and identi ed cell makers for each cluster (Supplementary Table 2). Cluster 4 expresses S100A8, S100A9, VCAN, and FCN1 which are associated with in ammatory monocytes [29,30], we thus de ned it as monocyte-like cells; Group 0 highly expresses a lot of MHC class II genes, such as HLA-DPB1, HLA-DPA1, HLA-DQB1 et al Cluster 1 expressed cytokines CCL2, CCL3, ADM et al, apolipoprotein genes APOC1, APOE, and pro-brotic genes SPP1, TIMP1 in control of ECM deposition [31]. Cluster 2, representative of tissue-resident macrophage, expresses previously unknown marker genes, such as PRSS1, CLPS, SYCN et al We con rmed high expression of PRSS1 in the normal pancreas tissue as shown by the immunohistochemical images deposited in Human Protein Atlas dataset ( Supplementary Figure 3a-c).…”
Section: Identi Cation Ofheterogeneity For Myeloid Cellsmentioning
confidence: 99%
“…Importantly, great progress has been made to identify reliable non-invasive biomarkers of both pathology progression and regeneration and drug efficacy. These will greatly help the translational assessment of therapy efficacy in the stem cell niche [ 42 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ]. In a general situation, even if it is not clear yet whether is the exhaustion of the satellite cell pool or niche disruption drives the pathological progression, we know that drugs acting either on the amelioration of the niche environment or satellite cells’ asymmetric division could be good candidates to slow down DMD.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in DMD patients, a single-nucleotide polymorphism (SNP, rs28357094T>G referred to as the G allele) in the promoter of OPN gene SPP1 has been identified as a genetic modifier of disease severity by modifying OPN activity [ 78 , 79 ]. It has been recently reported that, in the mdx mouse, OPN exacerbates the dystrophic phenotype by skewing macrophage polarization and promoting TGF-β1 activation via matrix metalloproteinase-9 (MMP-9) [ 80 ]. This extracellular protease and its inhibitor TIMP-1 are also strongly suggested as DMD progression plasma biomarkers.…”
Section: Pharmacological Approaches Targeting Niche Homeostasis: Wmentioning
confidence: 99%